Bankim Chandra : prophet of the Indian renaissance, his life and art - Das, Matilal (Calcutta : D.M. Library, 1938)
On the life and work of Bankim Chandra Chatterji, 1838-1894, Bengali author.
Microfilm.
Keywords: Authors, Bengali -- 19th century -- Biography